Biomimetic highly hydrophobic stearic acid functionalized MOF sponge for efficient oil/water separation - Tasmia Azam; Erum Pervaiz; Sarah Farrukh; Tayyaba Noor (Materials Research Express, 2021)
The field of oil/water separation has become a global concern with increase in oil/water pollution. Fabrication of highly hydrophobic surfaces by bio mimicking the ‘Lotus effect’ is turning out to be an area of active research in this regard. In current work ZIF-8 functionalized, stearic acid functionalized and composite, incorporation ZIF-8 and stearic acid in different deposition sequences, functionalized hydrophobic sponges were fabricated by changing the surface roughness and surface chemistry. The prepared sponges were analyzed by X-ray diffraction, scanning electron microscopy, fourier transmission infrared spectroscopy and sessile drop technique to conform the prerequisite of ‘lotus effect’. The important parameters i.e. water contact angle, oil absorption capacity and reusability of all prepared sponges were compared and it was found that the composite sponge that have first layer of ZIF-8 followed by second layer of stearic acid (S1Z8S) well inherited all properties of its parent components, showed high hydrophobicity with water contact angle of 140.8° and high absorption capacity for different oils/organic solvents ranging from 30.26 to 115.35 times its own weight as compared to other sponge samples and the this value of absorption capacity remained constant for 10 absorption/desorption cycles. Furthermore, it was found that coating another layer of stearic acid (S1S1Z8S) on this hydrophobic sponge increases hydrophobicity to 143.2° because of increase in surface micro-bumps but decreases oil absorption capacity. Being a three in one package with high hydrophobicity, high oil absorption capacity and excellent reusability S1Z8S can be an optimum candidate for large scale practical applications.